2020
DOI: 10.1177/0271678x20963404
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the potassium channel tracer [18F]3F4AP in rhesus macaques

Abstract: Demyelination causes slowed or failed neuronal conduction and is a driver of disability in multiple sclerosis and other neurological diseases. Currently, the gold standard for imaging demyelination is MRI, but despite its high spatial resolution and sensitivity to demyelinated lesions, it remains challenging to obtain specific and quantitative measures of molecular changes involved in demyelination. To understand the contribution of demyelination in different diseases and to assess the efficacy of myelin-repai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
99
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 32 publications
(101 citation statements)
references
References 65 publications
2
99
0
Order By: Relevance
“…Given these limitations, the use of PET radioligands that target proteins differentially expressed in demyelinated lesions appears to be a highly promising approach 6 as these channels significantly increase in expression and in accessibility upon demyelination 12,13,25 . In our previous work, we showed that [ 18 F]3F4AP can detect demyelinated lesions in rodent models of MS 8 and, more recently, that it has favorable pharmacokinetic properties in non-human primates and is highly sensitive to a focal brain injury 16 . In a parallel but related effort, we also investigated four novel derivatives of 4AP as potential candidates for imaging and/or therapy, among which 3MeO4AP was found to possess good binding affinity as well as suitable basicity (essential for binding) and lipophilicity (essential for brain penetration) 17 .…”
Section: Summary and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Given these limitations, the use of PET radioligands that target proteins differentially expressed in demyelinated lesions appears to be a highly promising approach 6 as these channels significantly increase in expression and in accessibility upon demyelination 12,13,25 . In our previous work, we showed that [ 18 F]3F4AP can detect demyelinated lesions in rodent models of MS 8 and, more recently, that it has favorable pharmacokinetic properties in non-human primates and is highly sensitive to a focal brain injury 16 . In a parallel but related effort, we also investigated four novel derivatives of 4AP as potential candidates for imaging and/or therapy, among which 3MeO4AP was found to possess good binding affinity as well as suitable basicity (essential for binding) and lipophilicity (essential for brain penetration) 17 .…”
Section: Summary and Discussionmentioning
confidence: 99%
“…However, in this work 90 min of data was used as the reference scan duration for the kinetic analyses because of increased statistical noise in late PET images as well as in the parent fraction measurements. According to the Akaike information criterion (AIC) 19 16 . We did not attempt coadministration of higher doses of nonradioactive 3MeO4AP as previous studies have shown that high doses of 4AP and related compounds can cause seizures 8,20 .…”
Section: C]3meo4ap In Nonhuman Primates: Analysis Of Arterial Bloodmentioning
confidence: 99%
See 3 more Smart Citations